Assume that $\mathbf{A}$, $\mathbf{B}$, and $\mathbf{A-B}$ are all positive definite Hermitian symmetric matrices of same dimensions. Prove that $\mathbf{B}^{-1}-\mathbf{A}^{-1}$ is positive definite.


We use the following useful fact:

Let $\mathbf{A}$ and $\mathbf{B}$ be HPD (Hermitian positive definite). Then $$\mathbf{A}\geq \mathbf{B} \quad \Leftrightarrow \quad \mathbf{I}\geq \mathbf{A}^{-1/2}\mathbf{B}\mathbf{A}^{-1/2}.$$

(Here $\mathbf{A}\geq \mathbf{B}$ means that $\mathbf{A}-\mathbf{B}$ is positive semidefinite and $\mathbf{I}$ is the identity matrix.)

Proof: $\mathbf{A}\geq \mathbf{B}$ if (and only if) for any $\mathbf{x}$ we have $\mathbf{x}^*\mathbf{A}\mathbf{x}\geq \mathbf{x}^*\mathbf{B}\mathbf{x}$. Since $\mathbf{A}$ is HPD, any $\mathbf{x}$ can be written as $\mathbf{x}=\mathbf{A}^{-1/2}\mathbf{y}$ and hence the previous inequality is equivalent to $$\mathbf{y}^*\mathbf{A}^{-1/2}\mathbf{A}\mathbf{A}^{-1/2}\mathbf{y}=\mathbf{y}^*\mathbf{I}\mathbf{y}\geq \mathbf{y}^*\mathbf{A}^{-1/2}\mathbf{B}\mathbf{A}^{-1/2}\mathbf{y}.$$ This means that $\mathbf{I}\geq \mathbf{A}^{-1/2}\mathbf{B}\mathbf{A}^{-1/2}$. Q.E.D.

Now we use twice the useful fact and the similarity relations to prove the statement of the question. Let $\mathbf{A}$ and $\mathbf{B}$ be HPD and $\mathbf{A}\geq \mathbf{B}$. Using the useful fact we have that $\mathbf{I}-\mathbf{A}^{-1/2}\mathbf{B}\mathbf{A}^{-1/2}\geq 0$. We have the following similarity relations: $$\mathbf{I}-\mathbf{A}^{-1/2}\mathbf{B}\mathbf{A}^{-1/2}\sim \mathbf{I}-\mathbf{A}^{-1}\mathbf{B}\sim \mathbf{I}-\mathbf{B}^{1/2}\mathbf{A}^{-1}\mathbf{B}^{1/2}.$$ Hence the matrix $\mathbf{I}-\mathbf{B}^{1/2}\mathbf{A}^{-1}\mathbf{B}^{1/2}$ is semidefinite. Using again the useful fact we have that $\mathbf{B}^{-1}\geq \mathbf{A}^{-1}$, that is, $\mathbf{B}^{-1}-\mathbf{A}^{-1}\geq 0$.

You can adapt it to your special case by replacing all occurrences of "$\geq$" and "semidefinite" by, respectively, "$>$" and "definite"; except in the proof of the useful fact where "any $\mathbf{x}$" must be replaced by "any nonzero $\mathbf{x}$".

  • $\begingroup$ What do you mean by similarity relation? Those steps where obscure to me. $\endgroup$ – user191919 Apr 15 '15 at 23:43
  • $\begingroup$ @user191919 $X\sim Y$ means "X and Y are similar", that is, $Y=PXP^{-1}$ for a nonsingular $P$. $\endgroup$ – Algebraic Pavel Apr 16 '15 at 9:06

First, suppose that $\|A-B\|<(\|A\|^{-1})^{-1}$. Writing $C=A-B$ we find that $$B^{-1} = (A-C)^{-1}=((I-CA^{-1})A)^{-1} = A^{-1}(I-CA^{-1})^{-1}$$ which expands into Neumann series $$B^{-1} = \sum_{n=0}^\infty A^{-1}(CA^{-1})^{n}$$ Hence, $$B^{-1}-A^{-1} = \sum_{n=1}^\infty A^{-1}(CA^{-1})^{n}$$ where every term in the series, e.g., $A^{-1}CA^{-1}CA^{-1}$, is positive, being a symmetric word in two positive matrices.

The general case reduces to the above by considering the finite sequence $$A_k= A-\frac{k}{n}(A-B), \quad k=0,\dots,n$$ where $n$ is sufficiently large so that $$\frac{1}{n}\|A-B\|<\|B^{-1}\|^{-1}$$ holds. Apply the above to $A_{k-1}$ and $A_{k }$, $k=1,\dots,n$. (This is possible because the smallest eigenvalue of $A_{k-1}$ is bounded from below by the smallest eigenvalue of $B$).


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.